THE ESSENCE OF ACCOUNTING PARADOXES (Economic journal of Lesya Ukrainka Volyn National University, 2022)
Accounting information serves as a primary source for the formation of financial statements, based on which further decisions are made. However, existing forms of financial reporting cannot fully meet the information needs of users. One of the reasons is the paradox of accounting information. Accounting paradoxes are a little-studied issue that requires proper coverage, first of all, the generation of theoretical and methodological framework, to better understand and optimize existing contradictions and controversial issues.The article describes the variety of methodological approaches to the scientific substantiation of the paradoxes of accounting information with their solutions and shortcomings.The paper highlights the economic essence of accounting paradoxes, their importance in the process of making effective management decisions, identifies the causes of formation, impact, and consequences of distortion of the information array in making rational management decisions. The role of the influence of accounting data paradoxes on the further activity of the enterprise is argued. The causal relationship between the possibility of distortion of accounting information at different stages of its formation depending on the object of accounting and its further transformation into management data is analyzed. As a result of the analysis of the outlined topic several solutions of problem questions are offered, namely: optimization of the accounting information, minimization of influence of paradoxes of the accounting information taking into account features of the account, expansion of the theoretical base.
Keywords: paradoxes of accounting information, management accounting, users of accounting information, quality of accounting information